Concentration anomalies of properties in Pb₁₋ₓGeₓTe solid solutions - Rogacheva, E. I.; Sinelnik, N. A.; Nashchekina, O. N. (My University, 1993)
The investigation of electrical conductivity, coefficient of thermal electromotive force, Hall coefficient, microhardness and mobility in Pb₁₋ₓGeₓΤe (x = 0 : 0.1) alloys in the temperature range of 77-300 K was carried out. Anomalies were detected in isotherms of properties in the vicinity of x = 0.008. The anomalies were treated as a manifestation of concentration phase transitions occurring in solid solutions of any kind and associated with existence of critical concentration (percolation threshold) at which the uninterrupted chain of interactions between impurity atoms is formed.